Bundling Strategies of Tourism Development Products in Bondowoso Regency, East Java, Indonesia - I Ketut Mastika; Sasongko Sasongko; Didik Eko Julianto; Pandu Satriya Hutama; Panca Oktawirani (International Journal of Applied Sciences in Tourism and Events, 2021)
This study focuses on developing bundling product strategies in the marketing of objects and tourism attractions. The purpose of this research is to examine the application of the bundling product concept as the development of the competitive strategy of tourist destinations. The research was conducted in Bondowoso district, East Java, Indonesia, which has various potential tourism assets. The method used is a descriptive method to analyze data and information relate to the opportunities and development of tourism in Bondowoso. The results indicated that the form of policy direction bundling strategy of Bondowoso tourism products have the opportunity to optimize the product bundling strategy with promotional packages to provide value of customer. The preference of the variety bundle is expected to be higher in the combined evaluation mode rather than in the separate evaluation mode. The Special Interest Tourism is the suitable type of tourism development. The attributes of the destination are expected to satisfy the needs of tourists also the aspects of performance quality which based on emotional motives. Marketing bundling products through promotion can be done by using e-marketing and viral marketing with several forms of social media.